Inhaled B7 alleviates bleomycin-induced pulmonary fibrosis in mice. (15th November 2021) - Liu, Yuhua; Wang, Shaofang; Gong, Xueqi; Wang, Yingshuo; Xu, Tonghui
Graphical abstract: Abstract: Treatment options for the progression of pulmonary fibrosis (PF), which ultimately causes respiratory failure, are limited. According to recent studies, recombinant human relaxin is potentially therapeutic against fibrosis and contraction during pulmonary damage. However, the production of recombinant H2 relaxin is laborious and expensive, limiting its extensive application. Thankfully, alternative research has revealed that treatment with a single-chain peptide of relaxin attenuates organ fibrosis in rodent models too, with the production of a single-chain peptide of relaxin simple and cheap; it could be therapeutic against idiopathic pulmonary fibrosis. Here, we explored the probable inhibiting effects of B7, a B chain of recombinant human relaxin, on bleomycin-induced pulmonary inflammation. Inhaled B7 efficiently reduced the number of inflammatory leukocytes and neutrophils in the bronchoalveolar lavage fluid of mice with bleomycin-induced PF, significantly improved the structure of the damaged alveolar, reduced collagen deposition, suppressed the main pathological features of idiopathic pulmonary fibrosis, i.e. the expression of both pulmonary α-smooth muscle actin and pulmonary vimentin, and inhibited the transcription of inflammation and collagen deposition-related mRNAs, including fibronectin, α-smooth muscle actin (α-SMA), interleukin-1β (IL-1β), interleukin-6 (IL-6), and alpha-1 type 1 collagen (Col-1a), and the expression of inflammation-related proteins, such as IL-1β, IL-6, chemokines (KC), TIMP metallopeptidase inhibitor 1 (TIMP-1), and hydroxyproline (Hyp). Overall, our findings suggest that inhaled B7 exerts beneficial effects against pulmonary fibrosis via attenuating inflammation. It could be developed into a simple, highly effective therapeutic approach for pulmonary fibrosis.